Social Preferences in Behavioral Economics: The Study of Reciprocal Altruism under Different Conditions - Yutong Zhang; Huannan Huang (Journal of Economics and Behavioral Studies, 2019)
Different external interventions prompt people to perceive different motivation which in turncauses different reactions. In our study, we propose that under different circumstances, the degree of the“reciprocal altruism heuristic” varies. This paper is aiming at carrying out an ultimatum game under twoscenarios and compares the results to demonstrate the effect of different external interventions on thetendency of reciprocal altruism. All 10 participants in the experiment, as a result, have shown differentinclination under the implementation of various external interventions, which strongly suggests the existenceof determinants that control the inclination of mutual cooperation and the provide insights for futurepsychological and educational related research to develop a more advanced system of human cognitivemodels under external interferences.